Prevalencia serológica de artritis encefalitis caprina (AEC) en apriscos de Cundinamarca, Colombia (1989)
Serologic prevalence of caprine arthritis encephalitis (CAE) virus was determined in 15 villages of Cundinamarca, Colombia by agar gel immunoditfusion test using Gp 135 reference protein. A sample of 200 serums was obtained according to a binomial design from 21 goat populations in the selected area. Positive reactors were detected in 26.5% of the tested animals and 14 out of 21 goat populations had positive animals. A significative association (P ≤ 0.01) was founded between infection, male sex, pure breed and breed crosses. No association was detected between prevalence and age. Prevention and control mesures against the disease are suggested.